Fabrication and characterization of herbal drug enriched Guar galactomannan based nanofibrous mats seeded with GMSC's for wound healing applications - Kalachaveedu, Mangathayaru; Jenifer, Preethi; Pandian, Ramajayan; Arumugam, Gnanamani (International journal of biological macromolecules, 2020)
Electrospun nanofibrous Guar gum/PVA based scaffold matrix incorporated with standardized extracts of four traditional medicinal plants of wound healing repute namely – Acalypha indica (A.i), Aristolochia bracteolata (A.b), Lawsonia inermis (L.i) and Thespesia populnea (T.p) was developed. Combinatorial ratio optimization of the extracts subject to their impact on nanofibre morphology, thermal and swelling stability resulted in a 4:4:1:1 blend of A.i, A.b, T.p and L.i at 20% of the total weight of the polymer mix. Dermal toxicity studies on female wistar rats established the nontoxicity of the generated Scaffold/Dressing. Cutaneous wound healing ability of Mesenchymal Stem Cells (MSC's) is well characterized to amplify their delivery and efficacy at the wound site. Apart from ease of accessibility, increased immune modulation of Gingival MSC's is their clear merit relative to those conventionally sourced from adipose tissues and bone marrow. A population of cells were isolated from discarded sample of human gingiva, following standard procedures and characterized as per minimal criteria as described by International Society for Cellular Therapy's (ISCT). The Cytocompatibility and proliferation of GMSC's were evaluated by MTT and Calcein AM assay demonstrating the viability of the seeded GMSC's up to 6 days. In vivo efficacy of the scaffold with and without GMSC's showed complete restoration of the tissue with minimal scarring. This investigation thus generated an herb drug enriched nanofibrous mat as a dressing and also a skin like scaffold with GMSC's, integrating the biological and technological benefits of herbal medicine and stem cell therapy respectively for skin regenerative applications.